THREE-DIMENSIONAL DENSITY MODEL OF THE NAZCA PLATE AND THE ANDEAN CONTINENTAL MARGIN - Tassara A.; Götze H.-J.; Schmidt S.; Hackney R. (My University, 2006)
We forward modeled the Bouguer anomaly in a region encompassing the Pacific Ocean (85°W) and the Andean margin (60°W) between northern Peru (5°S) and Patagonia (45°S). The three-dimensional density model that reproduces the gravity field is a continental-scale representation of density structure to 410 km depth that characterizes the mantle and crust of the oceanic Nazca plate, subducted slab and continental margin with a minimum number of bodies. We predefined the density of each body after studying the dependency of density on composition of crustal and mantle materials and pressure- temperature conditions appropriate for the Andean setting. A database of independent geophysical information constrains the geometry of the top of the subducted slab, locally the Moho of the oceanic and continental crusts and, indirectly, the lithosphere- asthenosphere boundary underneath the continental plate. Other boundaries, notably the intracrustal density discontinuity separating upper from lower crust below the continent, were not constrained and their geometry is the result of fitting the observed and calculated Bouguer anomaly during forward modeling. This contribution presents the model to the Andean geoscientific community and contains some tools, like a sensitivity analysis, that helps potential users of the model to interpret its results. We describe and discuss some of these results in order to illustrate the application of the model to the study of a wide range of phenomena (e.g., modification of oceanic plate structure by hot spots, shape of the subducted slab, thermal structure of the continental lithosphere, compensation mechanism and formation of orogenic relieve, causes of Andean segmentation. Copyright 2006 by the American Geophysical Union.